Socioeconomic and clinical aspects related to caries experience in schoolchildren treated at a Colombian university clinic - Romo Pérez, Camilo A. (2025)
Objective: To evaluate the relationship between caries experience and socioeconomic and clinical factors in children aged 5 to 12. Materials and methods: A cross-sectional study was conducted with a sample of 103 children aged 5 to 12 from Puerto Colombia (Colombia) between 2022 and 2023. Clinical, socioeconomic, and demographic data were obtained from medical records. Poisson generalized linear models with robust standard errors were fitted to evaluate the relationship between caries experience and both socioeconomic and clinical variables. Incidence rate ratios (IRR) and their 95% confidence intervals were presented for crude and adjusted models. Results: Caries experience was 94.85% (n = 98), with a median of 8 affected teeth (IQR = 5-11). Additionally, it was significantly higher in stratum 2 (IRR = 1.4; 95% CI: 1.042-1.956) in children without access to water and gas services (IRR = 2.29; 95% CI: 1.172-4.472), and in those with developmental defects of enamel (IRR = 1.188; 95% CI: 1.003-1.406), with poor oral hygiene (IRR = 1.68; 95% CI: 1.147-2.459), and in those who toothbrushed less than three times a day (IRR = 1.244; 95% CI: 1,027-1,507). Conclusion: Children with socioeconomic disadvantages, poor oral hygiene, and irregular toothbrushing practices exhibited a higher caries experience. It is necessary to address not only clinical, but also social and behavioral aspects in the prevention of childhood caries.